2015
DOI: 10.1371/journal.pone.0144619
|View full text |Cite
|
Sign up to set email alerts
|

Solution Radioactivated by Hadron Radiation Can Increase Sister Chromatid Exchanges

Abstract: When energetic particles irradiate matter, it becomes activated by nuclear reactions. Radioactivation induced cellular effects are not clearly understood, but it could be a part of bystander effects. This investigation is aimed at understanding the biological effects from radioactivation in solution induced by hadron radiation. Water or phosphate buffered saline was activated by being exposed to hadron radiation including protons, carbon- and iron-ions. 1 mL of radioactivated solution was transferred to flasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…When nitric oxide scavenger, cPTIO, was added to the transfer medium, chromosome aberration was not increased, suggesting that nitric oxide in irradiated medium was involved in inducing chromosome aberrations in non-irradiated cells. Maeda et al reported that irradiated medium can increase sister chromatid exchange in Chinese hamster ovary cells [17]. In our experiment, medium irradiated with 0.2 Gy Fe-ions without cells did not induce chromosome aberrations in non-irradiated cells.…”
Section: Resultssupporting
confidence: 51%
“…When nitric oxide scavenger, cPTIO, was added to the transfer medium, chromosome aberration was not increased, suggesting that nitric oxide in irradiated medium was involved in inducing chromosome aberrations in non-irradiated cells. Maeda et al reported that irradiated medium can increase sister chromatid exchange in Chinese hamster ovary cells [17]. In our experiment, medium irradiated with 0.2 Gy Fe-ions without cells did not induce chromosome aberrations in non-irradiated cells.…”
Section: Resultssupporting
confidence: 51%
“…Sister chromatid exchange was used for replicative stress analysis induced by PARP inhibitory effects by polyphenols (Figure 6). However, any genotoxic effects that directly or indirectly cause stress to cells can increase sister chromatid exchanges [21,22]. Therefore, observed elevation of sister chromatid exchange rate by tea polyphenols may not be solely from PARP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Using precision micro beams, low-dose internal radiation β-particles and hadron radiations, various investigators were able to find out several end-points and effects of bystander signaling in naïve mammalian cells. These include but are not limited to genetic and epigenetic transformations that according to some estimates were previously underestimated [9], genomic instability [10] which can cause lethal mutations and altered gene expression [11], activation of several signal transduction pathways in a dose dependent manner [6,12,13], γ-H 2 AX foci formation [14], delayed apoptosis [1,[15][16][17], sister chromatid exchanges (SCE) [6,18], micronucleation [17,19] and neoplastic transformations [11].…”
Section: Introductionmentioning
confidence: 99%